Oropharyngeal Decontamination with Antiseptics to Prevent Ventilator-Associated Pneumonia: Rethinking the Benefits of Chlorhexidine - Klompas, Michael (Seminars in Respiratory and Critical Care Medicine, 2017)
Daily oral care with chlorhexidine for mechanically ventilated patients is ubiquitous in contemporary intensive care practice. The practice is predicated upon meta-analyses suggesting that adding chlorhexidine to daily oral care regimens can reduce ventilator-associated pneumonia (VAP) rates by up to 40%. Close analysis, however, raises three concerns: (1) the meta-analyses are dominated by studies in cardiac surgery patients in whom average duration of mechanical ventilation is < 1 day and thus their risk of VAP is very different from other populations, (2) diagnosing VAP is subjective and nonspecific yet the meta-analyses gave equal weight to blinded and nonblinded studies, potentially biasing them in favor of chlorhexidine, and (3) there is circularity between diagnostic criteria for VAP and chlorhexidine; as an antiseptic, chlorhexidine may decrease the frequency of positive respiratory cultures but fewer cultures does not necessarily mean fewer pneumonias. It is therefore important to look at other outcomes for corollary evidence on whether or not oral chlorhexidine benefits patients. An updated meta-analysis restricted to double-blinded studies in noncardiac surgery patients showed no impact on VAP rates, duration of mechanical ventilation, or intensive care unit length of stay. Instead, there was a possible signal that oral chlorhexidine may increase mortality rates. Observational data have raised similar concerns. This article will review the theoretical basis for adding chlorhexidine to oral care regimens, delineate potential biases in randomized controlled trials comparing oral care regimens with and without chlorhexidine, explore the unexpected mortality signal associated with oral chlorhexidine, and provide practical recommendations.
Keywords: ventilator-associated pneumonia; oral care; chlorhexidine; quality improvement; ventilator bundles